Writing performance in the English proficiency test of new-intake university students - Abdul Malik, Faridah; Engku Ibrahim, Engku Haliza; Abdullah, Suhaila (CELPAD Research Unit, CELPAD, International Islamic University Malaysia, 2023)
The writing skill has always been dubbed as one of the most challenging skills. This is rightlyso as it is one of the two productive skills, speaking being the other productive skill.Nevertheless, students are most easily assessed through these productive skills. Thus, theimportance of mastery of these two skills. The objective of this paper is to investigate thewriting skill performance of new intake students in their English Proficiency Test which is arequired test upon entry to the International Islamic University Malaysia. Data was takenfrom results of the writing performance of 9,597 students across 10 cohorts (2016 – 2020) ofnew intake students. In general, the findings indicate that the mean band writingperformance of students over a five-year period was 5.294. The findings also show that theperformance of students differed significantly over the duration as well as between semesters.